Analisis Putusan Pengadilan Yang Mengembalikan Barang Bukti Dalam Tindak Pidana Di Bidang Perikanan - Eddy Rifai (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2013)
This study examines the return of court evidence in criminal acts in the field of fisheries. Type a descriptive study using the analytical approach of normative juridical approach and empirical jurisdiction. The results showed that the court ruling that restores used boats evidence of a crime in the field of fisheries compassionate grounds because the ship is the sole property of the convict to earn a living to feed their family law is not based on a logical construction. Against the perpetrators as well as ship owners should ship seized evidence to the state, while the evidence may ship returned to its owner by legal construction that ship owners not guilty conspiracy or involved in crime. Perspective court against criminal case evidence in fishing is to use the legal construction under the provisions of the legislation that provides protection to the owner of the evidence in criminal cases throughout the legislation does not specify otherwise. Therefore Fisheries Act determines that the evidence in the criminal case in the field of fisheries can be taken to the state or to be destroyed, then the judge should seize the evidence for the state if the offender is also the owner of the evidence, but if the evidence is that other people have not involved in the crime (no conspiracy between actors with the owner of the evidence), the evidence can be returned to the owner of the evidence.